RELEVANSI KONSEP PENDIDIKAN KARAKTER MENURUT IMAM IBNU JAMA’AH DALAM KITAB TAZKIRAH AS-SAMI’ WA AL-MUTAKALLIM FI ADAB AL-՝ALIM WA AL-MUTA՝ALLIM DENGAN PENDIDIKAN KARAKTER DI INDONESIA - Al Busthomi, Muhammad Yazid; Rifqi Junaidi, Mohammad (An-Natiq Jurnal Kajian Islam Interdisipliner, 2024)
Education in Indonesia currently emphasizes the importance of the character of the future generations. The government implements character education as a primary strategy to address the decline in character. The book "Tazkirah As-Sami’ Wa Al-Mutakallim Fi Adab Al-’Alim Wa Al-Muta’allim" by Imam Ibnu Jama’ah discusses ethics and morality in education with the aim of shaping better individuals in the future. This research aims to 1) analyze the concept of character education for students in the book "Tazkirah As-Sami’ Wa Al-Mutakallim Fi Adab Al-’Alim Wa Al-Muta’allim" by Imam Ibnu Jama’ah, and 2) evaluate its relevance to character education regulations in Indonesia. The research uses a qualitative approach and library research to produce descriptive data in the form of quotations. The results of the research indicate that: 1) The concept of character education in the book "Tadzkiratus Sami Wal Mutakallim" emphasizes the character of students towards themselves, their educators, and their subjects. 2) This concept aligns with the 18 core values outlined in the national character education regulation in Indonesia (Presidential Regulation No. 87/2017).